2017
DOI: 10.1016/j.jaubas.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adsorption and optimization of binary mixture of textile dyes: A factorial design analysis

Abstract: In this paper, a study of simultaneous adsorption of mixture dyes of Basic Blue 41 and Basic Yellow 28 in binary system was done using two types of activated carbon and compared with a single dye system in a batch mode. A competitive adsorption between the two cationic dyes was observed and it was noticed that Basic Blue 41 was favored. Kinetics of each dye in single and binary systems was found to follow pseudo-second-order rate kinetic model, with a good correlation (higher than 0.99). The single component e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…Positive and negative signs of their respective coefficients indicate that the parameter variation is either synergistic or antagonistic to the final desorption yield, respectively [40]. Accordingly, the model's coefficient and the adjusted determination coefficient (R 2 and R 2 adj , respectively) were calculated and found to be statistically significant at 98.961% and 96.630%, respectively, which confirms the good suitability of the theoretical model to the experimental results [41,42].…”
Section: Fitting the Design Modelsupporting
confidence: 57%
“…Positive and negative signs of their respective coefficients indicate that the parameter variation is either synergistic or antagonistic to the final desorption yield, respectively [40]. Accordingly, the model's coefficient and the adjusted determination coefficient (R 2 and R 2 adj , respectively) were calculated and found to be statistically significant at 98.961% and 96.630%, respectively, which confirms the good suitability of the theoretical model to the experimental results [41,42].…”
Section: Fitting the Design Modelsupporting
confidence: 57%
“…This is attributed to the fact that in the binary system, partial or total competitions between adsorbate ions for the binding sites on TMPAA surface occur and act as the entrapment-governing aspect. Besides, adsorption affinity of the modified polymer surface is mutually hindered by lateral interaction and rivalry between MG/MB components for the occupancy of sorption site [31,52]. A similar observation was reported Kurniawan et al (2012) for the uptake of basic dyes in a binary system by rarasaponin-bentonite [53].…”
Section: Resultsmentioning
confidence: 59%
“…Previous studies [7][8][9] concentrated on single adsorption systems using various adsorbents. Recently, by analyzing wastewater containing dyes, it was observed that many dyes coexist simultaneously; therefore, nowadays researches are focused on multicomponent dye adsorption [10][11][12]. Thus, finding a cost-effective way to eliminate such effluents from wastewaters has attracted a lot of attention these days [13].…”
Section: Introductionmentioning
confidence: 99%